(untitled) (Comprehensive Journal of Science, 2026)
Through the topic of the researchers paper it has become clear that individual constitutional appeals are among the most important legal mechanisms for protecting public rights and freedoms in contemporary constitutional systems. It is the path for individuals to access constitutional justice and it is characterized by being constitutional and that constitutional courts are the competent authorities to consider it after exhausting all procedures. The nature of individual constitutional lawsuits is that they are in ren lawsuits filed against constitutional texts and the plaintiff must have a personal and direct interest and the subject of the lawsuit must be the constitutional text. The Libyan constitutional judiciary is the primary instrument for upholding the rule of law through the constitutional chamber of the supreme court. Judicial review of laws is the true guarantee for individuals in protecting their rights and this review can be political or judicial. The 2017 draft constitution includes several fundamental individual rights and public freedom such as personal and civil rights and according to this draft if it is put to a referendum and approved an independent constitutional court was established to oversee constitutional matters and subsequent laws will define the mechanisms for appeal and the methods for filing lawsuits before this court.